Enhancing Speaking Confidence in Elementary Students through Task-Based and Communicative Approaches: A Community-Based Study at Rumah Tahfiz Daarul Uswah - Mutia Syarliza Nst; Sellyna Nova Insani; Sinta Fransiska Manik; Steven Gilbert Banjarnahor; Meisuri Meisuri (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Speaking fluency and confidence are crucial in second language acquisition, particularly for young learners who require engaging and interactive methods to enhance their communication skills. Traditional rote-based learning often fails to provide meaningful practice, leading to anxiety and lack of confidence in speaking. This study aims to evaluate the effectiveness of Task-Based Language Teaching (TBLT) and Communicative Language Teaching (CLT) in improving elementary students' confidence and fluency in speaking English. The research was conducted over eight sessions using a qualitative approach. Interactive teaching methods, including songs, roleplays, games, and self-description competitions, were implemented. Data were collected through observations and student progress evaluations, focusing on pronunciation, sentence construction, and fluency. The findings indicate that task-based activities significantly improved students’ confidence, fluency, and engagement. Initially, students faced challenges such as speaking anxiety, low participation, and disruptive behavior. However, through interactive strategies, they gradually overcame these difficulties. By the final session, most students demonstrated the ability to introduce and describe themselves fluently, showcasing the effectiveness of TBLT and CLT in ESL education. This study highlights the importance of student-centered, communicative learning approaches in fostering fluency and confidence in young ESL learners. The success of TBLT and CLT suggests that interactive, task-based instruction should be encouraged in ESL education to ensure learners can effectively use English in real-life situations.